Chado Controller: advanced annotation management with a community annotation system - Guignon, Valentin; Droc, Gaëtan; Alaux, M.; Baurens, F.C.; Garsmeur, O.; Poiron, C.; Carver, T.; Rouard, M.; Bocs, S. (Oxford University Press, 2012)
Summary: We developed a controller that is compliant with the Chado database schema, GBrowse and genome annotation-editing tools such as Artemis and Apollo. It enables the management of public and private data, monitors manual annotation (with controlled vocabularies, structural and functional annotation controls) and stores versions of annotation for all modified features. The Chado controller uses PostgreSQL and Perl.